OppaChinChingu / Nurul Jazmin Shamsudin... [et. al] - Shamsudin, Nurul Jazmin; Abdul Rasyid, Nursyafiqah; Za'aba, Munira; Syed Hisham, Syarifah Sumaiya; Abdul Rahman, Khairunnisa; Hasbullah, Muhammad Hariz Hazman (2021)
1.1 Brief description of the business and product concept The business that we are involved in is the Korean restaurant named OppaChinChingu Restaurant. Our restaurant is located in Bandar Baru Bangi Selangor. We chose this area because Bangi is the one favorable location for Malaysian who are staying in the nearest region like people who live near Putrajaya, Cyberjaya, Kajang, Serdang and anyone that lives nearest to our restaurant. OppaChinChingu Restaurant actually serves Korean dining with a great taste and we provide the varieties of menus for our customers. Our restaurant has a specialty product concept where we come out with the best root ingredients which keep the freshness and tasty in our meals. 1.2 Vision and Mission of the company As the same concept of the restaurant and the other businesses, we have already set up our own vision and mission for OppaChinChingu’s Restaurant. The Vision for our restaurant is to be well known organic Korean Cuisine in Malaysia. Meanwhile our mission is to provide our customers with great-tasting Korean food and drinks. We also want them to have good, respectful, friendly, and proper service while they are dining with us. 1.3 Restaurant’s core strength In order for us to achieve the success in our business, we would highlight our few components of strength and we also analyze the systematic planning throughout our Business Model Canvas (BMC). Our strategic management planning which highlights the Key Partners, Key Activities, Key Resources, Value Propositions, Customer Relationships, Channels, Customer Segments, Cost Structure, and also Revenue Streams. With all these templates and planning concepts we are extremely more confident to build this business as to compete with the other restaurant businesses. 1.4 Competitive Advantages OppaChinChingu’s Restaurant has differentiated from the competition by creating a unique and exciting fine dining atmosphere. Our restaurant will be set apart from other restaurants by its uniqueness and well thought out design and its exquisite decor. Each customer dining at OppaChinChingu’s Restaurant will enjoy an experience that is unlike anything they’ve experienced before. Our restaurant is also set apart through our commitment which provides the high product quality, not only in terms of food but also through offering friendly and high-quality service.